1991
DOI: 10.1016/0048-7333(91)90080-a
|View full text |Cite
|
Sign up to set email alerts
|

Academic research and industrial innovation

Abstract: for helpful comments, and to the 76 firms that provided the basic data used in this paper. A preliminary version of this paper was presented at the National Science Foundation, at Economics Day at the University of Pennsylvania, and at the 1988 annual meetings of the American Economic Association. ' Relatively few detailed studies of the contribution of academic research to industrial innovation have been carried out. Most seem to have focused on the drug industry. For example, see Mansfield et al. [15, ch. 81… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
431
0
36

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 927 publications
(479 citation statements)
references
References 2 publications
12
431
0
36
Order By: Relevance
“…However, for many smaller firms, the main sources of innovation are either internal or within their vertical supply chains (Mansfield, 1991). For instance, both 'specialized supplier' and 'supplier-dominated firms' rely on their vertical value chains for their innovative inputs (Pavitt, 1984) and are hence less likely to use academics as external collaborators.…”
Section: The Role Of Academic Consulting For Firmsmentioning
confidence: 99%
“…However, for many smaller firms, the main sources of innovation are either internal or within their vertical supply chains (Mansfield, 1991). For instance, both 'specialized supplier' and 'supplier-dominated firms' rely on their vertical value chains for their innovative inputs (Pavitt, 1984) and are hence less likely to use academics as external collaborators.…”
Section: The Role Of Academic Consulting For Firmsmentioning
confidence: 99%
“…Among the sectors analyzed by Jaffe (1989), drugs and medical technology showed the strongest influence of academic research on corporate patenting. In two different surveys, Mansfield (1991Mansfield ( , 1998 found the pharmaceutical industry had the highest percentage of new products based on recent academic research. Cohen et al (2002) reported that public research influenced new project ideas in the pharmaceutical industry more than in any other manufacturing industry.…”
Section: Introductionmentioning
confidence: 99%
“…2 Focusing on the pharmaceutical industry, Acemoglu and Linn (2004) built a theoretical model to explain the entry of new drugs into medical therapeutic markets. The 2 There are a number of other contributions to this literature including Mansfield (1991Mansfield ( , 1998, Narin et al (1997), Beise and Stahl (1999), and Arundel and Geuna (2004). Salter and Martin (2001) provide a survey.…”
Section: Introductionmentioning
confidence: 99%
“…Los estudios que han tratado de medir el efecto de la investigación en las Universidades públicas en la economía del país han mostrado una contribución positiva (ROOS e PIKE, 2011). Algunos de ellos muestran que: sobre el 10 por ciento de las innovaciones depende del apoyo de la investigación académica (MANSFIELD, 1991), el 20 por ciento de las innovaciones del sector privado se basan en investigaciones de Universidades públicas (TIJSSEN, 2002) y en la industria biomédica un incremento de 1 punto porcentual en la investigación académica conduce a un incremento de más de 2 puntos porcentuales en el número de compuestos…”
Section: Revisión De Literatura Y Hipótesisunclassified